Are There Limitations to Exercise Benefits in Peripheral Arterial Disease? - Zakari, Madaniah; Alsahly, Musaad; Koch, Lauren G.; Britton, Steven L.; Katwa, Laxmansa C.; Lust, Robert M. (Frontiers in Cardiovascular Medicine, 2018)
Substantial evidence exists indicating that regular exercise is essential in the promotion of health and treatment of disease. In fact, overwhelming evidence from various studies has revealed that regular exercise enhances both the quality of life was well as the life expectancy of an individual, and for that reason, exercise is now referred to as a “medicine”; as a drug. Yet, a significant subset of the population dies not respond to exercise, and in some settings, the stress induced by exercise may aggravate an underlying condition, rather than attenuate chronic disease. The focus of this review is new considerations in the field of exercise physiology, particularly including research that distinguishes between intrinsic aerobic capacity, as compared to active exercise training responses, in relation to effects on biological injury generally, and cardiovascular insults specifically. Distinctions between intrinsic capacity and active exercise responses will be reviewed. The limitations of intrinsic aerobic capacity in an experimental model in recovery using both a cardiac ischemia reperfusion model, as well as a hind limb occlusion model will be summarized, as well as the impact of superimposing active exercise in the context of both injury and intrinsic capacity. These will be discussed in the content of contraindications to exercise training, especially in patients suffering from different clinical disorders. The advantages of exercise of exercise will be summarized, but like other drugs, understanding the basis for non-responders and the consequences of prescribing in that setting, as well as the impact of dosing, timing, frequency and duration on the potential for detrimental side effects also will be indicated.